There are significant differences in World Congresses relevant to accounting in terms of the interest and the participation profile of countries - Güvemli, Oktay (De Computis, Revista Española de Historia de la Contabilidad., 2006)
Oktay Güvemli: There are significant differences in World Congresses relevant to accounting in terms of the interest and the participation profile of countries